Navigating Cultural and Contextual Complexities in Translating Uzbek Neologisms into English - Ergashev Tulkinjon Tukhtamurodovich (Indonesian Journal Publisher, 2025)
This study explores the translation of Uzbek neologisms into English, focusing on the influence of cultural and contextual factors. The analysis highlights how cultural differences, domain-specific characteristics, and the impact of social media shape translation strategies and semantic accuracy. Using corpus linguistics methods, the study examines neologisms across various sectors, including technology (80% translated via calquing or direct translation), economics (70% calquing), culture (60% descriptive translation), and social media (70% transliteration). Examples such as “xalqona” (folk-style/traditional Uzbek-style) and “xesh” (hashtag) illustrate the challenges of preserving cultural nuances and standardizing informal terms. Corpus analysis reveals that 40% of neologisms are included in Uzbek explanatory dictionaries, while only 30% have equivalents in Uzbek-English translation dictionaries, with 70% of social media neologisms absent. The findings propose corpus-based approaches and standardized equivalents to enhance dictionary coverage and optimize translation processes, contributing to the fields of linguistics and translation studies